Factors influencing functional outcomes following open reduction internal fixation of acetabular fractures. Issue 6 (June 2021) - Joseph, Noah M.; Flanagan, Christopher D.; Heimke, Isabella M.; Cho, Elizabeth; Pothireddy, Sahini; Scarcella, Nicholas; Vallier, Heather A.
Highlights: 283 patients completed MFA surveys after mean 66 months. The majority were male and sustained high energy injuries. PTA occurred in 25%, and HO occurred in 22% of all patients. Tobacco use, obesity, diabetes mellitus, PTA, and HO were associated with worse functional results on multivariable analysis. Abstract: Introduction: Recent large series of patient-reported outcomes after acetabulum fracture are limited, and potentially modifiable risk factors may be unidentified. The goal of this study was to describe patient and injury factors which negatively influence functional outcomes following operative management of acetabular fractures. Methods: 699 patients with acetabular fractures were treated with open reduction and internal fixation (ORIF). Musculoskeletal Function Assessment (MFA) questionnaire was completed after a minimum 12 months post-injury by 283 adults. MFA scores range from 1 to 100 and higher scores represent greater dysfunction. Factors were assessed for potential association with MFA scores, and univariate and multiple linear regression analyses were performed. Results: Survey respondents were more severely injured than non-respondents, with more chest injury (38% vs 22%, p<0.001) and higher Injury Severity Score (19.3 vs 16.8, p=0.003). Patients were 69% male with mean age 44.0 years. Approximately one-third were smokers (31%), while 14% had comorbid diabetes mellitus type II. The majority of injuries occurred during a motor vehicle collision (65%); low-energy mechanisms were rare (4.2%). The most common fracture pattern was isolated posterior wall (23%), followed by transverse/posterior wall (21%). Heterotopic ossification (HO) was noted in 22%: Brooker 1: 29.5%, 2: 23.0%, 3: 32.8%, and 4: 14.8%. Tobacco use (β = 18.4, p<0.001), obesity (β = 0.39, p=0.009), diabetes (β = 8.2, p=0.029), post-traumatic arthrosis (PTA) (β = 5.94 p=0.035), and increasing HO severity (β = 8.93, p<0.001) were independently associated with worse MFA scores. Tobacco use had the strongest association, followed by the severity of HO. Conclusion: In a large series of patient-reported functional outcomes following fixation of acetabular fractures, tobacco use, obesity, comorbid diabetes, PTA, and HO were associated with worse MFA scores. Further study to mitigate HO should be considered. Level of Evidence: III